Regional, sex, and age differences in diagnostic testing among participants in the NAVIGATE-ESUS trial. Issue 1 (January 2021) - Arauz, Antonio; Serrano, Fabiola; Pearce, Lesly A; Kasner, Scott E; Ameriso, Sebastian F; Toni, Danilo; Bereczki, Daniel; Siegler, James; Ruiz-Franco, Angélica; Cantú-Brito, Carlos; Czlonkowska, Anna; Lang, Wilfried; et al.
Background and aim: The diagnosis of embolic stroke of undetermined source (ESUS) is based on excluding other more likely stroke etiologies, and therefore diagnostic testing plays an especially crucial role. Our objective was to compare the diagnostic testing by region, sex, and age among the participants of NAVIGATE-ESUS trial. Methods: Participants were grouped according to five global regions (North America, Latin America, Western Europe, Eastern Europe and East Asia), age (<60, 60–74, and >75 years), and sex. Frequencies of each diagnostic test within areas of echocardiography, cardiac rhythm monitoring, and arterial imaging were described and compared across groups. A multivariable logistic regression model for each diagnostic test was fit to assess the independent influence of each of region, age, and sex and likelihood of testing. Results: We included 6985 patients in the analysis (918 from North America; 746 from Latin America; 2853 from Western Europe; 1118 from Eastern Europe; 1350 from East Asia). Average age (highest in Western Europe (69 years), lowest in Eastern Europe (65 years)), % females (highest in Latin America (44%) and lowest in East Asia (31%)), and use of each diagnostic test varied significantly across regions. Region, but not sex, was independently associated with use of each diagnostic test examined. Transesophageal echocardiography and either CT or MR angiogram were more often used in younger patients. Conclusion: Diagnostic testing differed by region, and less frequently by age, but not by sex. Our findings reflect the existing variations in global practice in diagnostic testing in ESUS patients.